Front-End Development on A Web-Based Teaching Material Repository System at SMK Diponegoro 1 Jakarta - Tina Audina; Hamidillah Ajie; Z.E. Ferdi Fauzan Putra (Journal of Computers for Society, 2024)
In the current digital era, information technology has greatly dominated the field of education, and the use of websites stands as a primary example. Websites play a crucial role in storing and conveying information. One such example is the school repository website. Having a storage medium for instructional materials can provide advantages to users, especially schools. Currently, at SMK Diponegoro 1 Jakarta, there is no dedicated storage for instructional materials. A single information system, Google Drive, is used to store all documents and information. The purpose of this research is to present and enhance the front-end appearance and functionality of the web-based Instructional Material Repository System. The development method employed is the Waterfall model, utilizing the Bootstrap framework and Javascript to construct a high-fidelity prototype of the system's front-end. Throughout the development process, black box testing was conducted to ensure the success of the system's functionality and usability. The testing results demonstrated that all tasks were successfully executed with a 100% success rate.